Electrochemical determination of serotonin in urine samples based on metal oxide nanoparticles/MWCNT on modiﬁed glassy carbon electrode - Fayemi, Omolola E.; Adekunle, Abolanle S.; Ebenso, Eno E. (Published by Elsevier B.V, 2020)
journal of Sensing and Bio-Sensing Research, vol. 13, 17-27P.